THE DERIVATIVE OF FUNCTIONS AND THE CEILING DETERMINANT OF A SQUARE MATRIX - Tilahun Muche; Willie Reynolds (IJRDO -JOURNAL OF MATHEMATICS, 2021)
Derivatives in calculus and Determinants of square matrices of any size in linear algebra are extensively used in STEM, Financial and Business elds to mention some. In this research paper, we develop mathematical formula to drill determinants for evaluating the derivatives of a function of higher order n. First, we introduce the Ceiling Determinant of a two by two matrix and extended this denition to nd the derivative of a function of n order. This new approach will help students to easily memorize the formula and apply to their major academic discipline. We have application examples on complex variable and geometry.